Interrelaciones de los atributos del producto y las preferencias intransitivas - Zoltán Veres; Petra Platz; Tamás Tarján (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– Consumers are thought to be rational in their choices. But sometimes their choices comprise intransitivities. Current paper presents a mathematically supported experimental study of consumers' intransitive preferences concerning product attributes. We used a personalized experimental design developed on the basis of Q methodology to maintain subjectivity. In our experimental study we are investigating intransitivity occurring in participants' preferences during selection between simple, medium complex, and complex products. By the Q method we gain the same number of less important (middle level) attribute dimensions for all participants. The participants' task is to make pairwise comparisons of preference between specific realizations of each product group. Since conjoint analysis is based on the measurement and testing of consumer preferences, reassessment of the phenomenon may have impact on marketing research methodology. This research is to test an experimental design which-with some adjustment-could be able to measure revealed preferences in a more precise way.
Keywords: M31; 330; Product attributes; Rating/ranking; Intransitive preferences